2006
DOI: 10.1111/j.1365-2036.2006.03080.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endoscopist withdrawal speed on polyp yield: implications for optimal colonoscopy withdrawal time

Abstract: SummaryBackgroundIn 2002, a U.S. Multi‐Society Task Force on Colorectal Cancer recommended that the withdrawal phase for colonoscopy should average at least 6–10 min. This was based on 10 consecutive colonoscopies by two endoscopists with different adenoma miss rates.AimsTo characterize the relationship between endoscopist withdrawal time and polyp detection at colonoscopy, and to determine the withdrawal time that corresponds to the median polyp detection rate.DesignProcedural data from out‐patient colonoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(104 citation statements)
references
References 23 publications
(30 reference statements)
8
93
1
2
Order By: Relevance
“…This study confirmed the work from the Mayo Clinic showed that 50% of polyps were diagnosed an average withdrawal time of 6.7 minutes, and 90% of polyps to a withdrawal time of 12 minutes (17). A recent observational study conducted among 315 gastroenterologists practicing in 17 U.S. states has confirmed the results of Simmons et al study, showing that those with an average withdrawal time equal to 6 min detected 1.8 times more polyps than other (18).…”
Section: The Time Of Withdrawal Of the Endoscopesupporting
confidence: 79%
“…This study confirmed the work from the Mayo Clinic showed that 50% of polyps were diagnosed an average withdrawal time of 6.7 minutes, and 90% of polyps to a withdrawal time of 12 minutes (17). A recent observational study conducted among 315 gastroenterologists practicing in 17 U.S. states has confirmed the results of Simmons et al study, showing that those with an average withdrawal time equal to 6 min detected 1.8 times more polyps than other (18).…”
Section: The Time Of Withdrawal Of the Endoscopesupporting
confidence: 79%
“…The expected incidence of CRC in one study, based on missed adenomas at screening colonoscopy, was 1.1 per 1000 persons within 5 years [3] . The effect of a variety of technical manoeuvres and mucosal enhancement technologies on adenoma detection and miss rates has been studied, including prolongation of colonoscope withdrawal time [4] , systematic patient positioning [5] , pancolonic dye-spray chromoendoscopy [6] , cap-assisted colonoscopy [7] , narrow band imaging (NBI) [8] and endoscopic trimodal imaging [9] , with variable degrees of success.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the possibility that longer withdrawal times were representative of more difficult rather than more careful examinations. Additionally longer withdrawal times have been found to correlate with the detection of smaller polyps (Simmons, Harewood et al 2006), not all of which might have been removed at colonoscopy.…”
Section: Withdrawal Timementioning
confidence: 99%
“…Endoscopists who took longer than 6 minutes to withdraw the colonoscope were found to have very low miss rates and more than 2-fold higher rates of detection of both small and large adenomas Barclay, Vicari et al 2006;Simmons, Harewood et al 2006). It has therefore been recommended that withdrawal of the colonoscope in patients without any prior colonic surgery should last at least 6 minutes on average (Rex, Petrini et al 2006).…”
Section: Withdrawal Timementioning
confidence: 99%